Fault Location Observability using Phasor Measurements Units via Semidefinite Programming - Alexopoulos, Theodoros A.; Manousakis, Nikolaos M.; Korres, George N. (IEEE access, 2016)
This paper presents a placement algorithm for fault location observability using phasor measurement units (PMUs) in the presence or absence of zero injection buses. The problem is formulated as a binary semidefinite programming (BSDP) model with binary decision variables, minimizing a linear objective function subject to linear matrix inequality (LMI) observability constraints. The model is extended to take into account the unavailability or limited capacity of communication links at some PMU installation buses. The BSDP problem is solved using an outer approximation scheme based on binary integer linear programming. The method is illustrated with a 6-bus test system. Numerical simulations are conducted on the IEEE 14-, 30-, and 57-bus standard test systems to verify the effectiveness of the proposed method.